Pendekatan Thought Situation Consequences (TSC) Framework untuk Mereduksi Grief - Herny Novianti (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2021)
This research aimed to know the role of TSC framework for reducing Grief. This study uses a qualitative approach with phenomenological method to explore the experiences and meanings of parents who lost their children in the tragic event of the trial court cases. The sample in this study were parent who lost their children, totally 2 participants. Data was collected by interviewed with open-ended question. Participant follow 7 stage of counseling of TSC Framework (creating rules, creating perceptions, creating self-talk). The results showed that participant have different reaction to grief, participant didn’t go automatically from the situation to the consequence of the situation. The role of TSC Framework in reducing grief can be seen from changing indicator denial, anger, bargaining, depression, dan acceptance. Recommendation showed for Islamic Counseling Guidance study program, and further research.